Frequency of Prediabetes in patients of HIV Infection Presenting at Tertiary Care Hospital - Muhammad Haroon Bilal, Muhammad Abdul Raziq, Muhammad Ajwad Humayon, Tariq Hussain, Muhammad Tahir, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To find out the frequency of prediabetes in patients of HIV presenting at tertiary care hospital. Study design: Cross sectional study. Place and duration: Department of Medicine, D.G Khan Hospital, D.G Khan. (January 2020 to December 2020) Methodology: Total 187 patients of HIV infection, age 20 years to 60 years both male or female with duration of HIV 10 years were selected and pre-diabetes was studies. Results: Total 187 patients of HIV infection was recruited for this study and prediabetes was assessed. Mean age and mean HIV infection duration was 37.81 ± 12.81 years and 5.31 ± 2.86 years. Prediabetes was noted in 63 (34%) patients. Male patients and female patients were 122 (65.24%) and 65 (34.76%) respectively. Prediabetes was found in 58 (47.54%) males and in 5 (7.69%) females. Prediabetes was significantly (P=0.000) associated with gender. Conclusion: This study showed a higher percentage of prediabetes among HIV infected patients. Most of the cases were belonged to 3rd and 4th decade of life. Males were more victim of HIV infection as compared to females and most of the males were prediabetics. No association of development of prediabetes with duration of HIV infected was noted. Keywords: Prediabetes, HIV infection, diabetes mellitus, IGT